Tracing Back the Evolutionary Route of Enteroinvasive Escherichia coli (EIEC) and Shigella Through the Example of the Highly Pathogenic O96:H19 EIEC Clone - Michelacci, Valeria; Tozzoli, Rosangela; Arancia, Silvia; D'Angelo, Alfio; Boni, Arianna; Knijn, Arnold; Prosseda, Gianni; Greig, David R.; Jenkins, Claire; Camou, Teresa; Sirok, Alfredo; Navarro, Armando; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Enteroinvasive Escherichia coli (EIEC) cause intestinal illness through the same pathogenic mechanism used by Shigella spp. The latter species can be typed through genomic and phenotypic methods used for E. coli and have been proposed for reclassification within E. coli species. Recently the first appearance of a highly pathogenic EIEC O96:H19 was described in Europe as the causative agent of two large outbreaks that occurred in Italy and in the United Kingdom. In contrast to Shigella spp and to the majority of EIEC strains, EIEC O96:H19 fermented lactose, lacked pathoadaptive mutations, and showed good fitness in extracellular environment, similarly to non-pathogenic E. coli, suggesting they have emerged following acquisition of the invasion plasmid by a non-pathogenic E. coli. Here we describe the whole genome comparison of two EIEC O96:H19 strains isolated from severe cases of diarrhea in Uruguay in 2014 with the sequences of EIEC O96:H19 available in the public domain. The phylogenetic comparison grouped all the O96:H19 strains in a single cluster, while reference EIEC strains branched into different clades with Shigella strains occupying apical positions. The comparison of the virulence plasmids showed the presence of a complete conjugation region in at least one O96:H19 EIEC. Reverse Transcriptase Real Time PCR experiments confirmed in this strain the expression of the pilin-encoding gene and conjugation experiments suggested its ability to mobilize an accessory plasmid in a recipient strain. Noteworthy, the tra region was comprised between two reversely oriented IS600 elements, which were also found as remnants in another EIEC O96:H19 plasmid lacking the tra locus. We hypothesize that an IS-mediated recombination mechanism may have caused the loss of the conjugation region commonly observed in EIEC and Shigella virulence plasmids. The results of this study support the hypothesis of EIEC originating from non-pathogenic E. coli through the acquisition of the virulence plasmid via conjugation. Remarkably, this study showed the ability of a circulating EIEC strain to mobilize plasmids through conjugation, suggesting a mechanism for the emergence of novel EIEC clones.